Applying UNESCO Guidelines on Mobile Learning in the South African Context: Creating an Enabling Environment through Policy - Aluko, Ruth (International Review of Research in Open and Distributed Learning, 2017)
Mobile broadband penetration is growing rapidly in Africa, and it offers vast opportunities for mobile learning. Together with its possibilities is the danger of overlooking standards related to its use. The United Nations Educational, Scientific and Cultural Organisation (UNESCO) has initiated work in this area focusing on African and Middle East (AME) countries. Countries are required to develop their own mobile learning policies. Examining information and communication technology (ICT) in the South African education environment, a qualitative approach is adopted using a literature review to assess the relevance and applicability of mobile learning in the broader education environment. A thematic analysis is used to identify themes from UNESCO’s guidelines, which are compared to the South African environment. Tracing the use of technology by an open distance learning (ODL) provider, an adapted framework was developed for mobile learning. This article argues the need to create an environment that enables sustainable mobile learning provision through policy development.